Intervensi Empati untuk Menurunkan Gejala Depresi pada Mahasiswa (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2023)
The prevalence of depression among college students is high. One of the factors that can exacerbate depressive symptoms is having interpersonal issues, such as a conflict with parents. Parent-children communication is challenging in Asian cultures due to family hierarchies and ambiguous communication. The condition is prone to misunderstandings when there is no empathic communication between parents and children. Empathy skill may be advantageous since it helps college students better understand their parents. To alleviate depressive symptoms, an empathy intervention is essential. This study investigates how empathy can lessen the symptoms of depression. A quasi-experimental one-group design (n = 9) was conducted in this study. The inclusion criteria for participants are college students in Indonesia with depressive symptoms (cut-off = 10). The participant who met the criteria received a total of five intervention sessions. Participants were recruited via social media and completed the Patient Health Questionnaire-9, Interpersonal Reactivity Index, and Satisfaction With Life Scale before and after the intervention to assess the change in depressive symptoms. Quantitative and qualitative result changes were examined. Using Repeated Measure Anova, depressive symptom is decreased (F(1.06,7.46) = 7.88, p = .02, η2 = .53) and satisfaction with life score is increased (F(2,14) = 8.39, p = .04, η2 = .54) after intervention. Furthermore, there is no significant change in empathic level (F(2,14) = 0.56, p = .58, η2 = .07). Qualitative data showed that empathic communication skills assist them in understanding their parents' intentions, improving their stress tolerance, and accepting their family situation. Therefore, empathy intervention benefits individuals with depressive symptoms who have conflicts with their parents.